Overweight and obesity prevalence among Indian women by place of residence and socio-economic status: Contrasting patterns from 'underweight states' and 'overweight states' of India. (August 2015) - Sengupta, Angan; Angeli, Federica; Syamala, Thelakkat S.; Dagnelie, Pieter C.; Schayck, C.P. van
Abstract: Evidence from developing countries demonstrates a mixed relationship of overweight/obesity with socioeconomic status (SES) and place of residence. Theory of nutrition transition suggests that over the course of development, overweight first emerges among rich and urban people before spreading among rural and poor people. India is currently experiencing a rapid rise in the proportion of overweight and obese population especially among adult women. Under the backdrop of huge socio-economic heterogeneity across the states of India, the inter-state scenario of overweight and obesity differs considerably. Hence, this paper investigates the evolution over time of overweight and obesity among ever-married Indian women (15–49 years) from selected 'underweight states' (Bihar, Orissa and Madhya Pradesh, where underweight proportion is predominant) and 'overweight states' (Kerala, Delhi and Punjab, where overweight is the prime concern), in relation to a few selected socio-economic and demographic indicators. This study analysed National Family Health Surveys- NFHS-2 (1998–99) and NFHS-3 (2005–06) following Asian population specific BMI cut-offs for overweight and obesity. The results confirm that within India itself the relationship of overweight and obesity with place of residence and SES cannot be generalized. Results from 'overweight states' show that the overweight problem has started expanding from urban and well-off women to the poor and rural people, while the rural-urban and rich-poor difference has disappeared. On the other hand in 'underweight states' overweight and obesity have remained socially segregated and increasing strongly among urban and richer section of the population. The rate of rise of overweight and obesity has been higher in rural areas of 'OW states' and in urban areas of 'UW states'. Indian policymakers thus need to design state-specific approaches to arrest the rapid growth of overweight and its penetration especially towards under-privileged section of the society. Highlights: Overweight is spreading faster among rural people in 'overweight states'. Overweight is expanding at a high rate among poorer people in 'overweight states'. In 'underweight states', overweight is emerging among the urban and rich segment. There is mixed association between overweight prevalence and socioeconomic status.